Encouraging Pro-Environmental Behavior Through Environmental Communication Based on Tri Hita Karana - Octaviani, Natasya; Meliana, Magsyanda; Yudhistira, Putu Gde Arie (Politeknik Negeri Bandung, 2024)
Tri Hita Karana (THK), a core Balinese philosophy emphasizing harmony between religious, human, and environmental values, is a guiding principle in tourism development and environmental communication. This study analyzed the effectiveness of environmental communication practices rooted in THK at Melasti Beach. Employing a qualitative case study approach, data collection methods included observation, document analysis, and in-depth interviews with key stakeholders such as the customary leader of Ungasan Village, Melasti Beach managers, local community members, and tourists. Data triangulation was used to validate findings and ensure reliability. The research findings reveal that environmental communication based on THK principles has effectively fostered pro-environmental behaviors among stakeholders. By integrating spiritual reverence, social cohesion, and ecological care, implementing THK-oriented communication strategies at Melasti Beach has preserved the natural environment and strengthened community engagement and cultural integrity. This study underscores the potential of local wisdom like THK to inspire sustainable tourism practices and environmental stewardship in Bali and beyond.